KERJA SAMA PROJECT ARAFURA AND TIMOR SEAS ECOSYSTEM ACTIONS (ATSEA) DALAM MENINGKATKAN KERAGAMAN BIOTA LAUT DI WILAYAH ARAFURA PERIODE 2019 -2022 - Kania Salsabila (2023)
The sea is an important element for human life. Apart from being a source of life, the sea is also a source of food, access to transportation, trade, recreation areas, as well as being a dividing and unifying area for the nation. Along with its development, the sea has increased its function with the discovery of the resources contained therein. The waters of the Arafura Sea and the Timor Sea are sea areas that have extraordinary natural wealth. This region is directly bordered by four countries: Australia, Indonesia, Timor Leste and Papua New Guinea. This water area is famous for its diversity of marine life and is home to 50% of the world's coral reef population. However, in addition to its natural wealth, this sea area is facing threats of destruction and extinction. Departing from this situation, the four border countries decided to form a cooperation forum which eventually materialized in the Cooperation Project Arafura and Timor Seas Ecosystem Actions (ATSEA). This cooperation project is divided into two phases of cooperation, the first phase running from 2010 - 2014 and the second phase running from 2019 - 2024. From the ongoing cooperation, the countries have succeeded in identifying the root causes of the problems they are facing and determining what strategies and actions need to be taken. taken to resolve the problems that occurred in the Arafura Sea and Timor Sea areas. Although in progress, this collaboration is still experiencing several obstacles so that there are several problems that have not been resolved properly. The concept used in this study is the concept of international cooperation. This study uses qualitative methods with case study analysis. The results of this study show that the collaboration that was established in the ATSEA Project can be said to be in accordance with the main objectives of this collaboration, namely to restore, enhance and ensure the sustainability of the diversity of marine life in the Arafura Sea and Timor Sea regions.